Smart Buildings| An Integrative Double Skin Facade Damper System for Safety and Energy Efficiency - Zhang, Rui (University of New Hampshire, 2018)
A smart building is an intelligent living space that elevates energy efficiency, comfort and safety. The word “smart” implies that the building would have a decision making system that can sense its conditions and reacts to them in an automatic and effective manner. Modem buildings contain many subsystems and, thus, to achieve automation, sophisticated sensing networks and robust control systems must be installed. The proposed research focuses on integrating several building systems—structural health monitoring (SHM), and structural and environmental controls—and explores synergy among them to improve efficiency and sustainability of buildings. More specifically, an integrative, smart building system is developed by combining double skin façades and mass dampers in buildings to improve both safety and energy efficiency. Double skin façade systems protect and insulate buildings with two heavy glass layers between which air is allowed to flow for ventilation. By enabling movements in the outer façade skin, the façade can be used as a mass damper that reduces structural vibration and damage during earthquakes and wind storms. The added mobility also leads to innovative ways to control ventilation rate and improve energy efficiency by adjusting the gap size between the outer and inner skins. In this dissertation research, the energy impact of the integrated system was first investigated. Then both passive and active structural control strategies were experimented and analyzed on a six-story shear building model. Results indicated the proposed system can significantly reduce structural response under the earthquakes excitations. In addition, the sensor networks and actuators introduced by the active structural control system were utilized for structural health monitoring purposes. The actuators provided harmonic excitations while the acceleration data were collected by the sensor networks to perform damage diagnosis. Finally, since typical SHM systems require large networks of sensors that are costly to install, this dissertation research also examined using smartphones as alternative sensors. Using the aforementioned six-story experimental structure, a sensing system consisted of six smartphones was tested and proven effective in detecting structural damage. The experimental result demonstrates that further developments of smartphone SHM can lead to cost-effective and quick sensor deployments.